2019
DOI: 10.26434/chemrxiv.7581578.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triplex Hybridization of siRNA with Bifacial Glycopolymer Nucleic Acid Enables Hepatocytetargeted Silencing

Abstract: We have submitted a new manuscript, entitled “Triplex hybridization of siRNA with bifacial glycopolymer nucleic acid enables hepatocyte-targeted silencing” for consideration as an article in ACS Chemical Biology. My co-authors, Xin Xia, Zhun Zhou, Chris DeSantis, John Rossi and I have agreed on the submission of this manuscript. In the current manuscript, we demonstrate the utility of polyacrylates modified with both an artificial base-triple and a sugar (GalNAc) to serve as an siRNA packaging and delivery pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…21 22 23 Prior work has demonstrated that α-peptide bPNAs can intracellularly target oligo T/U internal loops in DNA and RNA 9 24 as well as unstructured oligos. 2 4 6 Triplex hybrid stems are functionally compatible with native nucleic acid architectures and can noncovalently target ligands to U-rich internal loops (URILs) in small interfering RNA duplexes, 25 as well as long noncoding RNAs (lncRNAs). 24 Recently, we discovered that backbone structured bPNAs containing just two base-tripling residues 26 27 can readily engage with unstructured oligos as well as structured URILs in lncRNA; moreover, affinity is increased when the dipeptide bPNAs are cyclized to a diketopiperazine (DKP) (Scheme 1 ).…”
mentioning
confidence: 99%
“…21 22 23 Prior work has demonstrated that α-peptide bPNAs can intracellularly target oligo T/U internal loops in DNA and RNA 9 24 as well as unstructured oligos. 2 4 6 Triplex hybrid stems are functionally compatible with native nucleic acid architectures and can noncovalently target ligands to U-rich internal loops (URILs) in small interfering RNA duplexes, 25 as well as long noncoding RNAs (lncRNAs). 24 Recently, we discovered that backbone structured bPNAs containing just two base-tripling residues 26 27 can readily engage with unstructured oligos as well as structured URILs in lncRNA; moreover, affinity is increased when the dipeptide bPNAs are cyclized to a diketopiperazine (DKP) (Scheme 1 ).…”
mentioning
confidence: 99%